Molecular Biology of Ornamental Plants - Song, Aiping; Chen, Yu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Relative to model plants, ornamental plants have many special characteristics, such as their flower color, shape and fragrance. Furthermore, these traits are unique and complex compared to different plants. With the development of sequencing technology and omics tools, core regulatory networks and genes related to specific traits were discovered in a variety of ornamental plants. These research methods have enriched the exploration of the regulatory mechanisms of ornamental traits and provided elite candidate genes for directional breeding. This Special Issue "Molecular Biology of Ornamental Plants" covers 13 ornamental plant species, including 7 woody flowers, 3 perennial flowers, 1 aquatic flower and 2 herbs. The research topics include flower color, abiotic stress, species diversity, plant development and research protocol innovation. The research methods integrate the latest methods of bioinformatics and molecular biology.